Supporting The Company's Investment Decision With The Method Simple Multi Attribute Rating Technique (SMART ) - Eriana, Emi Sita (LPPM, 2025)
Advancing the company, PT FAC, which is engaged in the processing of snacks, in an effort built to support the performance of the management company, conducting a decision support system (SPK) to expand investment by choosing various alternatives including car purchases, land purchases, expanding warehouses, maintaining systems and information technology facilities and developing new products. This is a consideration for management in making previous decisions that are the reason for investment within 10 years. The SMART method was chosen as a supporting method in selecting alternatives because it allows for effective monitoring of progress by requiring measurable goals. An individual or team can easily determine the extent to which a goal has been achieved. The purpose of this study is to help determine whether corrective action or adjustment to the results of decisions taken based on methodological steps is necessary. The results of the calculation were obtained from the calculation of normalization and weighting that the highest yield of profitable investment in 10 years that PT FAC will take is the maintenance of systems and technological facilities (A3) with a value of 0.85, and the highest value of alternative 4 (A4) is developing new products with 0.670.